Die wese van godsdienssin - ’n empiriese studie - Kok, J. C. (Koers, 1993)
In this article the following issues concerning the essence of religiosity are considered: faith, trust, decision making, knowledge of principles, commitment, direction, hope, peace, meaning and security. The respondents used in this study were politicians, businessmen and teacher educators from all sectors and regions of South Africa. Higher order factor analysis and item analysis were used to evaluate the validity and reliability of the questionnaire. Subsequently differential differences were investigated by applying Hotelling's T-square test followed by the Student t-test as well as Multivariate Analysis of Variance (ANOVA) and Scheffe. Significant differences in the degree of religiosity were found between language and religious groups, as well as between respondents with different educational qualifications and between those living in urban and rural areas. Ministers of religion should note that it is essential to guide believers to a greater commitment and to the religious seeking of meaning and peace. The correct knowledge of and insight into the essence of religiosity will lead to attaining this goal.